2018
DOI: 10.1177/0950422218812631
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education as human capital: Implications for youth self-employment and conflict mitigation in Sub-Saharan Africa

Abstract: Previous research has focused on stable developed economies to predict that human capital and entrepreneurship education (EE) provision at the higher education (HE) level will positively affect entrepreneurial success. This article draws on the outcome of recent EE projects in two HE institutions in a conflict-torn northern Nigeria as a proxy to advocate the introduction of entrepreneurship as a compulsory component into the secondary school curriculum in Sub-Saharan Africa. Using semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 89 publications
(101 reference statements)
2
19
0
Order By: Relevance
“…Likewise, Cui et al (2019) mention that entrepreneurship education can foster student inspiration, mindset, attitudes and intentions, as well as the initiation of new companies. Besides, empirical work by Anosike (2019) highlights a considerable nexus between entrepreneurial education and HC outputs, such as attitudes and skills linked with entrepreneurship. The pedagogical in entrepreneurship education also helps students to maintain inspiration, motivation and interest, promoting the greater presumption of success (Nabi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Cui et al (2019) mention that entrepreneurship education can foster student inspiration, mindset, attitudes and intentions, as well as the initiation of new companies. Besides, empirical work by Anosike (2019) highlights a considerable nexus between entrepreneurial education and HC outputs, such as attitudes and skills linked with entrepreneurship. The pedagogical in entrepreneurship education also helps students to maintain inspiration, motivation and interest, promoting the greater presumption of success (Nabi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presented results are essential to promote the methodological perspectives in future studies. Since human capital studies that only concentrate on or measure formal education are limited (Anosike, 2019;Sánchez, 2013;Wang, Li, Lien, 2016), a holistic and integrated approach incorporates formal education, work experience, and conventional knowledge would create a more accurate picture. According to our conclusions, future research should focus on operationalizing human capital not only through school or university education but also through a broader range of expertise and experience.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the papers focused only on formal education, including school, university education attainment, and post-school training (Wang, Li, Lien, 2016). Several authors observed specific formal education, such as entrepreneurial education (Anosike, 2019;Sánchez, 2013), which promotes entrepreneurship-specific competencies and entrepreneurial intention. In addition to the quality of human capital, attention has been paid to the quantity of human resources, especially in the process of households' economic activities diversification (Bhandari, 2013;Khai, Danh, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the theoretical lens through which EE is understood (Marvel et al, 2016). Human capital refers to individual's stock of skills, competencies, knowledge and attributes acquired through experience, exposure, training and education, and it is key to the entrepreneurial process and success (Anosike, 2019). EE is vital to human capital development.…”
Section: Entrepreneurship Education (Ee)mentioning
confidence: 99%